Sensitivity of Leafy Vegetables to Simulated Mesotrione Residues in the Soil - Milena Radivojević; Dejan Nedeljković; Katarina Jovanović-Radovanov (Horticulturae)
Mesotrione is a triketone herbicide widely used for weed control in maize (Zea mays L.). In a bioassay conducted under controlled conditions, the simulated residual effects of mesotrione on leafy vegetables, including chard, lettuce, spinach, and endive were evaluated. The herbicide was applied at nine concentrations (0–240 µg a.i./kg soil), with the highest corresponding to the recommended field application rate. Nonlinear regression analysis was used to describe the relationship between morphological (shoot fresh weight) and physiological (pigment content) parameters as a function of herbicide dose. Shoot fresh weight was a more sensitive parameter than pigment content with mean EC50 ± SE values of 23.9 ± 3.5 (chard), 34.3 ± 7.7 (lettuce), 13.2 ± 2.4 (spinach), and 990.3 ± 3921.5 (endive) µg a.i./kg soil, indicating that spinach is the most sensitive and endive the most tolerant species. A mesotrione residue level equivalent to EC20 for shoot fresh weight corresponds to approximately 2, 4, 6, and 29% of the recommended application rate of mesotrione at which spinach, chard, lettuce, and endive (respectively) can be safely sown. Therefore, spinach, chard, and lettuce are not suitable substitutes for maize when the latter fails and should not be sown after silage maize. In such cases, only endive appears to be a viable alternative without the risk of crop injury.